Incidence Matrices of Directed Graphs of Groups and their up-down Pregroups - Wadhah S. Jassim (Sultan Qaboos University Journal for Science, 2017)
The aim of this work is to give a definition of the incidence matrices of the directed graph of groups, construct an up-down pregroup of the incidence matrices of the directed graph of groups and then give an algorithm for the up-down pregroup of the directed graph of groups.